(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Technology is rising quickly in enterprise and manufacturing in the 21st century. Education becomes more important in this century to ensure that students are trained, willing to invent, develop, collaboration and learn how to make use of their life skills. The complex meaning and excellence capabilities for their future generate challenges. The definition of skills of the 21st century has become extremely relevant as it represents changing job demands as well as the changing position of education. We will study the integration of expertise in school programs in the 21st century that concludes that those who commit themselves to the holistic view of education have plenty of research work to do, experience sharing, capacity building and advocacy around the potentials and needs of all countries, irrespective of their contexts, to move in this direction.